Implementación de rincones de trabajo para el desarrollo psicomotriz en los niños y niñas del primer año de básica de la escuela “Once de Noviembre” ubicado en la parroquia Ignacio Flores del Cantón Latacunga provincia de Cotopaxi durante el año lectivo 2012 – 2013 - Albán Arguello, María Cristina (2015)
This research is related to the implementation of workshops that were executed in places of work to optimize the psychomotor development of children / as school "Once de Noviembre" of the canton Latacunga; It took into account a conceptual review, critical and analytical work on the corners, its structure, adequacy and materials able to stimulate the psychomotor development of preschool children, using appropriate in each corner from a scientific perspective based on criteria of several authors playful strategies both psychologists and educators who have contributed significantly to the management of places of work and their benefits in the psicomottíz development of infants. The research methods were facilitated deductive - inductive and analytical - synthetic. The first start conceptualizing the categories of research, analysis on a specific group of children and the development of alternative solutions; and second because each research question was analyzed to draw conclusions and recommendations; to determine the reality in which the institution, where the technical aspect was analyzed at the discretion of the lady principal of the school "Once de Noviembre" unfolds, teachers gentlemen, parents and direct observation of children about the existence and use of the corners aimed at psychomotor development of children work. The alternative proposal was made to improve psychomotor development of children the same that was entitled "Implementation Guide didactic work corners for developing motor skills in children in the first year of basic" same guiding workshops to work in corners, developing motor skills of children, including psychomotor corner, the corner of the dramatization, music corner and the corner of the plastic.